Lingual canal incidence in lower incisors: A literature review (Research, Society and Development, 2025)
Introduction: Lack of anatomical knowledge of root canals can compromise endodontic treatment. Cone-Beam Computed Tomography (CBCT) is essential for analyzing canal morphology. Objective: To review the literature regarding the number and configuration of canals in mandibular incisors, based on Vertucci’s classification, and to discuss the clinical considerations of this morphology. Methods: Studies evaluating permanent human mandibular incisors using CBCT were included, excluding review articles. The descriptors “Mandibular incisor,” “Root canal,” and “Cone-Beam Computed Tomography” were used in the PubMed, Embase, and Lilacs databases on March 6, 2025, with no restrictions on time or language. A total of 14 studies were identified, of which 28 published between 2013 and 2025 were selected. Results: A higher incidence of two canals was observed in lateral mandibular incisors (75%) and central mandibular incisors (17.86%), with 7.14% not specifying the type of incisor. Vertucci’s type III configuration was the most prevalent. Regarding sex, 64.28% of the studies reported no significant difference, while 17.86% indicated a higher incidence in men and 17.86% in women. Age range was not analyzed. Conclusion:The mandibular lateral incisor shows a higher incidence of two root canals, predominantly Vertucci’s type III configuration, with no significant sex differences. CBCT is essential for identifying anatomical variations, enhancing endodontic treatment.